Transaction costs and networks - Blois, Keith (Strategic Management Journal, 1990)
Abstract The study of networks is attracting considerable attention. One of the difficulties of such studies is that techniques of analysis, concepts, and models developed in a variety of disciplines are used. The dangers of using the work of other disciplines are illustrated by considering the way in which the concept of transaction costs has been used.